Characteristics of the Joint Combustion of Brown Coal and Sewage Sludge under Nonisothermal Heating Conditions; Solid Fuel Chemistry; Vol. 56, iss. 5 - Zhuykov A. V. Andrey Vladimirovich (2022, 2022)
Title screen